1996
DOI: 10.1002/(sici)1098-2752(1996)17:8<425::aid-micr1>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Secondary ischemic tolerance improved by administration of L-NAME in rat flaps

Abstract: Nitric oxide (NO) under basal conditions is an important regulator of vascular tone. Under ischemic conditions, however, NO can combine with superoxide anion to produce the damaging hydroxyl free radical. The current project observes the effect of inhibiting NO production (L-Nitro-amino-methyl-arginine, L-NAME) on flaps rendered ischemic by secondary (2 degrees) venous obstruction. Eighty rats had 3 x 6 cm skin flaps based on the epigastric vessels. Primary (1 degree) ischemia was produced by arteriovenous occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
3

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
(20 reference statements)
0
1
3
Order By: Relevance
“…Other studies report a possible cytotoxic action of NO producing damaging hydroxyl free radicals in models of venous flap obstruction. 30 However, these findings can neither be confirmed nor be disproved by our results, since our model did not focus on venous ischemia.…”
Section: Discussioncontrasting
confidence: 67%
“…Other studies report a possible cytotoxic action of NO producing damaging hydroxyl free radicals in models of venous flap obstruction. 30 However, these findings can neither be confirmed nor be disproved by our results, since our model did not focus on venous ischemia.…”
Section: Discussioncontrasting
confidence: 67%
“…44 Treatment with L-arginine in the drinking water and autologous bone marrow cells increased perfusion in a hind-limb ischemia model. 45 Nonselectively inhibiting NOS using L-NAME decreased tissue preservation under ischemic conditions, 46 and eNOS-null mice have defective recovery of blood flow following hind-limb ischemia. 47 These results are consistent with the effects of L-NAME to decrease and ISDN to increase tissue survival in our ischemic flap model.…”
Section: Discussioncontrasting
confidence: 64%
“…Other studies reported a possible cytotoxic action of NO in producing damaging hydroxyl free radicals in models of venous flap obstruction. 73 However, these findings can be neither confirmed nor disproved by our results, since our model did not focus on venous ischemia.…”
Section: The Role Of Nitric Oxide In the Preconditioning Mechanismcontrasting
confidence: 70%